Quality Change of Soysauce Produced by Home Scale Industry During Three Months of Storage - Henky Isnawan Hendritomo (Jurnal Teknologi dan Industri Pangan, 2003)
The investigation was conducted to study of the change of soysauce quality during three months of storage. The soysauce quality observed included, sucrose, protein, NaCl content and total microflora such as molds and bacteria. The result showed that the a mount of sucrose and protein of the soysauce were content was 67,8% and 3,07%, respectively after 3 months of storage the sucrose and protein content decreased to 58,8%, and 2,3%. During storage, the number of bacteria and mold increased from 2.1 x103 to 3.7 x 103 and 4.0 x102 to 6.1 x103 CFU/ml, respectively. It was concluded that separation process at 100 mesh was ineffective to reduce bacteria and mold. When compared to SNI, the soysauce quality is still good and safe to consume. Key words : Saoysauce, koji, Aspergillus oryzae, moromi